2000
DOI: 10.1002/1097-0010(200006)80:8<1162::aid-jsfa613>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic models of non-enzymatic browning in apple puree

Abstract: The effects of thermal treatments on 11 °Brix apple puree were studied at temperatures from 80 to 98 °C. Colour changes (measured by re¯ectance spectroscopy, colour difference, L*, a* and b* and the evolution of 5-hydroxymethylfurfural (HMF) and sugars (hexoses and sucrose) were used to evaluate non-enzymatic browning. A kinetic model based on a two-stage mechanism was applied to the evolution of colour difference and a*. A ®rst-order kinetic model was applied to L* evolution, while the evolution of absorbance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
52
3
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(68 citation statements)
references
References 18 publications
10
52
3
3
Order By: Relevance
“…In addition, the BI of both processed juices significantly increased with the increase of storage time for which pasteurized juice showed higher rate of changing BI than another juice (slopes of the trend-lines). High BI of pasteurized juice might be a reflection of high b* and low L parameters, which could primarily be due to an influence of Maillard condensation (Ibarz et al, 2000). Other researchers, for instance, Polydera et al (2005) pasteurized (80°C/1 min) and pressurized (600 MPa/40°C/4 min) orange juices stored at 0-30°C for 60 days.…”
Section: Results and Discussion Color Stabilitiesmentioning
confidence: 64%
“…In addition, the BI of both processed juices significantly increased with the increase of storage time for which pasteurized juice showed higher rate of changing BI than another juice (slopes of the trend-lines). High BI of pasteurized juice might be a reflection of high b* and low L parameters, which could primarily be due to an influence of Maillard condensation (Ibarz et al, 2000). Other researchers, for instance, Polydera et al (2005) pasteurized (80°C/1 min) and pressurized (600 MPa/40°C/4 min) orange juices stored at 0-30°C for 60 days.…”
Section: Results and Discussion Color Stabilitiesmentioning
confidence: 64%
“…Notwithstanding these differences, the reflectance spectra of the two lots were identical and both showed, when compared to the TQ drink, a decrease in the R values, in the 560-740 nm range. Ibarz et al [33,34] found a decrease in the reflectance values of apple and pear purees as the heating time increased, mainly in the 520-600 nm range, corresponding to green and orange hues, suggesting that the decrease in R values indicated that upon heating there was a more pronounced degradation of greenish and yellow pigments of apple and pear purees.…”
Section: Influence Of Pasteurization On Fruit-rcw Beveragescolormentioning
confidence: 99%
“…Na Tabela 1 estão apresentados os resultados do estudo do tratamento térmico para os açúcares, pode-se constatar que na primeira hora tivemos um decréscimo acentuado para a sacarose, o que podemos creditar ao caráter ácido do suco clarificado de caju que em conjunto com a temperatura favorece a hidrólise da sacarose resultando nas duas unidades monossacarídicas que a compõe (glicose + frutose) [3,6,9,10]…”
Section: -Açúcaresunclassified
“…Observou-se também um concomitante aumento do teor de 5-HMF com a diminuição dos açúcares, constatação que está de acordo os resultados relatados por ARE-NA, FALLICO, MACCARONE [3] e IBARZ, PAGAN, GARCIA [6]. A relação quantitativa dos açúcares (glicose + frutose)/ sacarose (ver Tabela 1) apresentou-se como uma opção alternativa para o controle de qualidade da cajuína.…”
Section: -Açúcaresunclassified
See 1 more Smart Citation